The Charter Granted by Their Majesties King William and Queen Mary to the Inhabitants of the Providence of the Massachussets Bay in New England 272-73 (1726) - (:unkn) unknown (My University, 1719)
An Act in Further Addition to an Act for Erecting a Powder House in Boston: That, from and after the publication of this Act, no gunpowder shall be kept on board any ship, or other vessel, lying to or grounded at any wharf within the port of Boston. And if any gunpowder shall be found on board such ship or vessel lying aground, as aforesaid, such powder shall be liable to confiscation, and under the same penalty, as if it were found lying in any house or warehouse. And be it further enacted by the authority aforesaid, that no powder be carried through any town upon trucks, under the penalty of ten shillings per barrel for every barrel of powder so conveyed, and so proportionally for smaller cask.
Keywords: GUNPOWDER - TRANSPORTATION